2022
DOI: 10.55218/jasr.202213129
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Particles Characteristics, Temperature Sensitivity and Morphology of Peg/Poly (Nipam-Co-Amps) Microgels

Abstract: The temperature sensitive copolymer of microsize hydrogels consist of N-isopropylacrylamide (NIPAM) and 2- acrylamido-2 methylpropanesulphonic acid (AMPS) have been synthesized by soap free emulsion polymerization method in the presence of polyethylene glycol (PEG) as macro initiator and N, N´-methylenebisacrylamide (NMBA) as crosslinker. In this work, Dynamic Light Scattering (DLS), Transmission Electron Microscope (TEM) and Atomic Force Microscope (AFM) technique were used for structural analysis of microgel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
2
0
0
Order By: Relevance
“…It was observed that the mean diameter of particles obtained from DLS (hydrodynamic diameter) was more as compared to the crystal size obtained from XRD. The increased diameter of the particles as obtained from DLS can be attributed to the formation of a thin layer of liquid on the surface of NPs 57 . This increased hydrodynamic diameter as compared to crystallite size obtained from XRD confirms the hydrophilic nature of the particles 58 .…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…It was observed that the mean diameter of particles obtained from DLS (hydrodynamic diameter) was more as compared to the crystal size obtained from XRD. The increased diameter of the particles as obtained from DLS can be attributed to the formation of a thin layer of liquid on the surface of NPs 57 . This increased hydrodynamic diameter as compared to crystallite size obtained from XRD confirms the hydrophilic nature of the particles 58 .…”
Section: Discussionsupporting
confidence: 53%
“…The increased diameter of the particles as obtained from DLS can be attributed to the formation of a thin layer of liquid on the surface of NPs. 57 This increased hydrodynamic diameter as compared to crystallite size obtained from XRD confirms the hydrophilic nature of the particles. 58 This was further justified from the contact-angle measurements.…”
Section: Discussionsupporting
confidence: 52%